The comparative performance of mutual building societies and stock retail banks - Valnek, Tomas (Journal of Banking & Finance, 1999)
We investigate the comparative performance of mutual building societies and stock retail banks in the UK. Our results indicate that mutual building societies appear to have outperformed stock retail banks, suggesting that the benefits of mutual organisations may outweigh those of stock organisations. These benefits stem from the merger of the owner and the depositor functions, and from their homogeneous clientele: costs related to conflicts between different classes of claimholders and conflicts within the single class of claimholders are thus avoided.